(untitled) (Revista Brasileira Multidisciplinar, 2026)
The National Policy for the Homeless Population, Decree No. 7,053, dated December 23, 2009, defines the homeless population as a heterogeneous group characterized by extreme poverty, weakened family ties, and the lack of conventional housing. This group uses public streets and degraded areas as living spaces, as well as temporary shelter units for overnight stays. The municipality in the current study has a Specialized Reference Center for the Homeless Population, which aims to address the medium-complexity needs of this population, with an emphasis on ensuring their social rights. The homeless population has specific health and social needs, which justifies the importance of this work. The objective was to understand the perspective of social assistance professionals regarding the health needs of the homeless population. The research was exploratory, using semi-structured interviews, which were recorded and transcribed on a mobile phone, with professionals from the Center for the homeless population who met the inclusion criteria. Through these interviews, the knowledge of the Center workers about the health needs of the homeless population was observed, and the challenges related to these needs were analyzed. The study concluded that the focus is on access to health services, adherence to treatments, substance abuse, stigma, and street-based healthcare services.